Design of Silicon Photonics External Cavity Laser - Zheng, Jiamin (My University, 2014)
The development of silicon photonics, driven by the increasing demand for bandwidth from data centre applications, is receiving growing attention. As a result of the indirect bandgap of Si material, it is more practical to heterogeneously incorporate the laser source than fabricate directly on Si. Of all the approaches, an external cavity laser (ECL) approach which consists of III-V gain material and Si photonic integrated circuit (SiPIC), is a flexible and cost effective solution. This thesis captures theoretical and experimental work on the design of SiPIC ECLs. In addition, a four wavelength laser source using an SiPIC ECL scheme is proposed and studied.
The theoretical tool is first introduced on the traveling wave model (TWM) and it is numerically solved with FDTD in Matlab. A digital filter approach is used to describe the feedback from an SiPIC external cavity, where the phase delay of the digital filter is investigated and utilized to set the cavity length.
The III-V gain chip and SiPIC are then examined separately for their characterization, along with the coupling and feedback requirements in an ECL design.
Lastly, experiments are conducted to demonstrate the feasibility of four wavelength ECLs and SiPIC ECLs.
Keywords: Silicon Photonics; External cavity laser; Data Centre; Traveling wave modeling; Electromagnetics and photonics; Electromagnetics and photonics